Formulation of a system of indicators of information protection quality in automatic systems of numerical control machines for advanced material processing. (2019) - Parashchuk, Igor; Kotenko, Igor
Abstract: The paper investigates an approach aimed at obtaining the optimal system of information protection quality indicators in automatic systems of universal machines and processing centers with numerical programmed control, used in modern materials processing technologies. The formulation of the optimal system of information protection quality indicators is carried out taking into account the fuzziness of the source data. The mechanisms of the formulation of the system of the information security quality indicators are proposed. The system claims to be optimal in terms of reliability, informativeness and efficiency of collecting and processing observation data.